U-Pb geochronology of crustal evolution and orogeny Contributions from Caledonide Spitsbergen and the Precambrian West Troms Basement Complex, North Norway - Myhre, Per Inge (Universitetet i Tromsø, 2011)
The papers of this thesis are not available in Munin: 1. Myhre, P.I., Corfu, F. & Andresen, A.: 'Caledonian anatexis of Grenvillian crust: a U/Pb study of Albert I Land, NW Svalbard', Norwegian Journal of Geology (2008) Vol. 89, pp. 173-191. Available at http://www.geologi.no/data/f/0/20/00/8_2401_0/NJG309_P._I._Myhre_et_al_screen.pdf 2. Per Inge Myhre, Fernando Corfu, Steffen Bergh: 'Palaeoproterozoic (2.0–1.95 Ga) pre-orogenic supracrustal sequences in the West Troms Basement Complex, North Norway', Precambrian Research (2011) vol. 186, pp.89–100. Available at http://dx.doi.org/10.1016/j.precamres.2011.01.003 3. Per Inge Myhre, Fernando Corfu and Steffen Bergh: 'U-Pb geochronology along a Neoarchaean geotransect in the West Troms Basement Complex, North Norway' (manuscript). 4. Bergh, S.G., Kullerud, K., Armitage, P.E.B., Zwaan, K.B., Corfu, F., Ravna, E.J.K. & Myhre, P.I.: 'Neoarchaean to Svecofennian tectono-magmatic evolution of the West Troms Basement Complex, North Norway', Norwegian Journal of Geology (2010) Vol. 90, pp 21-48. Available at http://www.geologi.no/data/f/0/20/23/8_2401_0/NJG_1_2010_Bergh_sc.pdf